2015
DOI: 10.1007/s13313-015-0361-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of Fusarium root rot in soybean caused by Fusarium equiseti or Fusarium graminearum using loop-mediated isothermal amplification (LAMP) assays

Abstract: Rapid diagnostic assays for Fusarium root rot in soybean, caused by Fusarium equiseti or Fusarium graminearum were developed using the target gene CYP51C. Both assays amplified the target gene in 60 min at 62°C, after which they were assessed for specificity and sensitivity. Specificity was evaluated against other Fusarium spp., other fungal species, and oomycetes. A positive yellow-green color (by the naked eye) or intense green fluorescence (under ultraviolet light) was observed only in the presence of F. eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Data from this study indicated that the detection limit of the LAMP assay was 1 pg genomic DNA, in accordance with other reports of LAMP methods (Lu, Zhang, Wang, & Zheng, ), and the sensitivity was greater than the previous report for LAMP assay used to detect A. citrulli (Oya et al, ). Compared to the conventional PCR, LAMP provides reliable detection as specific as conventional PCR but increases the sensitivity by 100‐fold.…”
Section: Discussionsupporting
confidence: 91%
“…Data from this study indicated that the detection limit of the LAMP assay was 1 pg genomic DNA, in accordance with other reports of LAMP methods (Lu, Zhang, Wang, & Zheng, ), and the sensitivity was greater than the previous report for LAMP assay used to detect A. citrulli (Oya et al, ). Compared to the conventional PCR, LAMP provides reliable detection as specific as conventional PCR but increases the sensitivity by 100‐fold.…”
Section: Discussionsupporting
confidence: 91%
“…We found many fungal genera/species in healthy soybean roots that are well-known pathogen species of soybean and/or other plants such as wheat. For example, Fusarium, Macrophomina, Rhizoctonia, and Alternaria cause root rot or foliar and stem blight in soybeans (Lu et al 2015a;Lu et al 2015b;Ramos et al 2016;Yamamoto et al 2017). Our preliminary pathogenicity assays for some of these isolates showed that many of them may be truly asymptomatic in soybean seedlings, while some were able to cause disease symptoms, indicating that they may be latent pathogens that cause disease under stress or at a later time during plant growth.…”
Section: Discussionmentioning
confidence: 80%
“…2015a), F. equiseti and F. graminearum (Lu et al. 2015b). However, a report of LAMP assay for detecting F. culmorum is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…lycopersici (Almasi et al 2013), F. oxysporum f. sp. ciceris (Ghosh et al 2015), F. oxysporum (Lu et al 2015a), F. equiseti and F. graminearum (Lu et al 2015b). However, a report of LAMP assay for detecting F. culmorum is lacking.…”
Section: Introductionmentioning
confidence: 99%